Analisis Kinerja UPJA Menunjang Kegiatan Usaha Tani Padi - Sugiarto Sugiarto (Jurnal Penelitian Pertanian Terapan, 2010)
The existence of UPJA institute has been known by farmers, especially farmer nirigation land since last 3 decades. UPJA institute which has been known by farmers identical with alsintan managemant to suport agriculture effort, especially rice plant in villages. This resarch was done in two provinces, Central Java and South Sulawesi. The resarch showed score of B/C ratio wich was gained bu using alsintan UPJA reach 2,5=3,5.This score was reached because partisipation of farmer using UPJA more effecient and economic scale more beneficial. On other hand, the perception of alsintan availability was needed as an anticipation to production increasing and lack of labor in villages. So that, existence of UPJA, either managed by group or individually are nedeed as suprot to agriculture work from land management, maintanance, irigation, haverst and post harvest. Beside that, giving security guarante in production proses and to press haverst fail. Keywords: Existence of UPJA, Rice farmer.